Mapping haemodynamic changes with rapid sequence induction agents in the emergency department. (22nd September 2021) - Freeman, Jessica; Alkhouri, Hatem; Knipp, Robert; Fogg, Toby; Gillett, Mark
Abstract: Objective: Patients intubated in the ED are at an increased risk of post‐intubation hypotension. However, evidence regarding the most appropriate induction agent is lacking. The present study aims to describe and compare the haemodynamic effect of propofol, ketamine and thiopentone during rapid sequence induction. Methods: This is an observational study using data prospectively collected from the Australian and New Zealand Emergency Department Airway Registry between June 2012 and March 2019. The distribution of induction agents across medical and trauma patients were obtained with descriptive statistics. The relationship between induction agent, dose and change in pre‐ and post‐intubation systolic blood pressure (SBP) was described using multivariable logistic regression. The SBP pre‐ and post‐intubation was the primary measure of haemodynamic stability. Results: From the 5063 intubation episodes, 2229 met the inclusion criteria. Of those, 785 (35.2%) patients were induced with thiopentone, 773 (34.7%) with propofol and 671 (30.1%) with ketamine. Of the included population, 396 (17.8%) patients experienced a reduction in pre‐intubation SBP exceeding 20%. Both propofol ( P  = 0.01) and ketamine ( P  = 0.01) had an independent and dose‐dependent association with hypotension, noting that a higher proportion of patients induced with ketamine had a shock index exceeding 0.9. Conclusion: Propofol was associated with post‐intubation hypotension and it is recommended clinicians consider using the lowest effective dose to reduce this risk. Reflecting its perceived haemodynamic stability, patients who received ketamine were more likely to have a higher shock index; however, there was also an association with post‐intubation hypotension. Abstract : This multicentre study from Australia and New Zealand used prospectively collected data to determine haemodynamic changes in rapid sequence induction agents used in the ED. It found that propofol and ketamine had a dose‐dependent association with a reduction of systolic BP of >20% post‐intubation. Thiopentone was not associated with a reduction in BP.